Expatriados: percepção da legislação tributária e da gestão de recursos humanos - Ribeiro, Ana Paula Martins (2014)
The phenomenon of globalization and the advancement of new technologies became the world becoming smaller, causing the distances between countries, people and organizations become ever smaller, with this come the need for "global business". Brazil, now no longer a labour exporter Brazil has become one of the leading destinations in foreigners. The number of expatriates working in Brazil is growing, according to information provided by the Ministry of Labour and Employment, 2009 were issued approximately 43,000 permits for work , comparing with the year 2013 , which were issued more than 62 000 authorizations , if affirm that there was an increase of approximately 45 % . Some organizations have established some policies which include aspects: tax, labour, social, and manage costs. The principal objective of this study was to describe the perceptions of foreigners in Brazil, not only in terms of adaptation and cultural aspects, but also with respect to tax matters. The subjects were 5 professionals 5 different foreign companies that have branches in Brazil. Data collection was conducted through semi-structured personal interviews, according to a predetermined script. Among the biggest difficulties reported to the language barrier, cultural adaptation and tax aspects, often unknown. Among the contributions of this study is to compile the tax aspects relating to foreign and immigration. This work can also be replicated for more than 12 months, thus enabling accompany the perception of foreign, for long term